Effects of Resistance Exercise on Balance Ability: Systematic Review and Meta-Analysis of Randomized Controlled Trials - Sarabon, N.; Kozinc, Z. (Life, 2020)
With this systematic review, we explored whether resistance exercise (RE) could be used to improve balance in addition to muscular strength and power. Scientific databases were searched for randomized controlled trials that investigated the effects of RE on the performance of various balance tests. Studies were considered if they involved healthy participants of any age group. Thirteen studies were included in the meta-analysis. The results showed moderate to large improvements in balance ability following RE in older adults, as reflected in functional reach test (mean difference (MD): +4.22 cm, p < 0.001), single-leg standing test (MD: +1.9-37.6 s, p < 0.001) and timed-up-and-go test (MD: -0.55 s; p = 0.002). Moderate to large improvements following RE were seen in adults in star excursion balance test (MD: +4.09-5.17 cm; p = 0.001-0.020), but not for Y-balance test score (MD: +4.94%, p = 0.14). The results implicate that RE interventions may significantly improve balance ability in adults and older adults. Therefore, RE could be used to improve balance in these populations, while further studies are needed to investigate children populations. Performing RE alone could be a time-efficient compromise for individuals who are unwilling or unable to perform large volumes of exercise or different exercise modalities.